Assessment of the Impact of Global Competitiveness in University Education: the Nigerian Experience - Ifeakor , Comfort ,Amaechi; Ifeakor , Comfort ,Amaechi; Obiadazie, Regina Eyiuche; Anujeonye , Christiana Nneamaka (African Journal of Education,Science and Technology (AJEST), 2014)
Globalisation is a growing phenomenon in higher education institutions in Nigeria and the world at large. It is very closely intertwined with internationalisation. It refers to the phenomenon where the borders separating countries are disappearing. This allows the flow of science, technology, engineering, mathematics, economy, knowledge, people, values and idea across borders. Globalisation affects each country in different ways due to each nation‟s individual history, traditions, cultures, resources and priorities. Its determinants include competition over funding, superior educational infrastructure, quality teachers across the world, top international students, academic content, entrepreneurship education and great impact on Information and Communication Technology (ICT). This paper assessed the impact of global competitiveness in Nigerian universities. The study was a descriptive study carried out in three Universities –federal, state, private- in South East zone of Nigeria. Random sampling technique was used to select three hundred (300) respondents. Two research questions guided the study. Questionnaire was developed for data collection. Data were collected and analysed using means and standard deviation. The findings revealed that global competitiveness should be the growing trend in all aspects of academic endeavours. Based on the findings, it was recommended that Nigerian universities should strive to attract funds from government and other funding agencies, contend for top international students and produce graduates for global market